Cortometraje con integración de animación CGI para la concientización del riesgo de distracciones al conducir - Carrasco López, Andrés Fernando (2017)
This project aims at making a short film that seeks to create awareness among drivers of Ecuador, where a survey showed that other short films made abroad did not exercise greater impact when viewed because of being made in very different foreign locations and vehicles that are not used in everyday life, so with the mixture of audiovisual production with three-dimensional animation it is shown how a few seconds of distraction can end in a terrible accident.